2010
DOI: 10.1016/j.arr.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia as a cytoprotective strategy in ischemic tissue injury

Abstract: Hypothermia is a well established cytoprotectant, with remarkable and consistent effects demonstrated across multiple laboratories. At the clinical level, it has recently been shown to improve neurological outcome following cardiac arrest and neonatal hypoxia ischemia. It is increasingly being embraced by the medical community, and could be considered an effective neuroprotectant. Conditions such as brain injury, hepatic encephalopathy and cardiopulmonary bypass seem to benefit from this intervention. It's rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 142 publications
0
38
0
Order By: Relevance
“…Inflammatory markers decrease, as well as microglial activation, leucocyte infiltration, MMP activation and BBB disruption. In addition, hypothermia suppresses apoptotic cell death, decreases mitochondrial release of cytochrome C and apoptosis inducing factor (see for review (Tang and Yenari, 2009)). Cell survival pathways are upregulated and appear to contribute to the multiplicity of neuroprotective mechanisms.…”
Section: Moving Forward: Charting a Course Toward New Stroke Therapiesmentioning
confidence: 99%
“…Inflammatory markers decrease, as well as microglial activation, leucocyte infiltration, MMP activation and BBB disruption. In addition, hypothermia suppresses apoptotic cell death, decreases mitochondrial release of cytochrome C and apoptosis inducing factor (see for review (Tang and Yenari, 2009)). Cell survival pathways are upregulated and appear to contribute to the multiplicity of neuroprotective mechanisms.…”
Section: Moving Forward: Charting a Course Toward New Stroke Therapiesmentioning
confidence: 99%
“…[27][28][29][30][31] For example, induced hypothermia has been routinely used in surgery since the early 1950s. 30 It is a well-established means of cytoprotection in which, lowering temperature slows metabolism and renders cells in a suspended state to maintain cell survival. However, only a few clinical studies have convincingly demonstrated a role in humans.…”
Section: Adenosine Provides Tissue Protection Under Hypoxiamentioning
confidence: 99%
“…Although many prevention methods such as chemoprevention, risk-reduction surgery, molecular genetics, epidemiology, and imaging have been used to reduce the incidence of cancer, few have paid attention to mild hypothermia (32-35ºC) as a strategy to prevent tumor cell adhesion and extravasation although mild hypothermia (32-35ºC) has been studied to improve outcome from cardiac arrest, brain trauma, stroke, hypoxic encephalopathy of neonates, spinal cord injury, open cardiac surgery, and other ischemic tissue injury for a long time (18). One of the important mechanisms is that mild hypothermia inhibits the inflammation response which contributes significantly to secondary injury after ischemia (19,20).…”
Section: Introductionmentioning
confidence: 99%